2020
DOI: 10.1186/s41984-019-0072-5
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope Assisted Microvascular Decompression: Are the Advantages Still Worthy Towards More?

Abstract: Background Microvascular decompression is the definitive treatment of various neuralgias affecting cranial nerves. The compression on a cranial nerve could be at the root entry zone, especially the trigeminal nerve. Endoscope-assisted microsurgery may help avoid missing a hidden vascular structure. Study design Retrospective clinical case series. Patient and methods Twenty-five patients with facial pain and five patients with hemifacial spasm constituted this study. FIESTA MRI was the pre-operative neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…All domains of general function and facial function scores were significantly improved immediately postoperative and progressive improvement was witnessed until the end of follow up duration. [18] reported a female sex predominance [76.0%] among 25 patients with TN, and SCA was the commonest compressed vessel [88%]. Yadav et al [19] found 28/51 patients [54.9%] were V2 and 20/51 were V3 [39.2%].…”
Section: Discussionmentioning
confidence: 99%
“…All domains of general function and facial function scores were significantly improved immediately postoperative and progressive improvement was witnessed until the end of follow up duration. [18] reported a female sex predominance [76.0%] among 25 patients with TN, and SCA was the commonest compressed vessel [88%]. Yadav et al [19] found 28/51 patients [54.9%] were V2 and 20/51 were V3 [39.2%].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an endoscopically assisted minimally invasive retrosigmoid approach was the ideal option for treating both pathologies for experienced surgeon. 11) Compression of the facial nerve at the REZ by the vessel responsible for HFS can be assessed by MRI, which also allows detection of a cerebellopontine angle tumor. 12) This information is important for surgical decision-making.…”
mentioning
confidence: 99%